Differential magnesium implant corrosion coat formation and contribution to bone bonding. Issue 3 (7th November 2016) - Rahim, Muhammad Imran; Weizbauer, Andreas; Evertz, Florian; Hoffmann, Andrea; Rohde, Manfred; Glasmacher, Birgit; Windhagen, Henning; Gross, Gerhard; Seitz, Jan‐Marten; Mueller, Peter P.
Abstract: Magnesium alloys are presently under investigation as promising biodegradable implant materials with osteoconductive properties. To study the molecular mechanisms involved, the potential contribution of soluble magnesium corrosion products to the stimulation of osteoblastic cell differentiation was examined. However, no evidence for the stimulation of osteoblast differentiation could be obtained when cultured mesenchymal precursor cells were differentiated in the presence of metallic magnesium or in cell culture medium containing elevated magnesium ion levels. Similarly, in soft tissue no bone induction by metallic magnesium or by the corrosion product magnesium hydroxide could be observed in a mouse model. Motivated by the comparatively rapid accumulation solid corrosion products physicochemical processes were examined as an alternative mechanism to explain the stimulation of bone growth by magnesium‐based implants. During exposure to physiological solutions a structured corrosion coat formed on magnesium whereby the elements calcium and phosphate were enriched in the outermost layer which could play a role in the established biocompatible behavior of magnesium implants. When magnesium pins were inserted into avital bones, corrosion lead to increases in the pull out force, suggesting that the expanding corrosion layer was interlocking with the surrounding bone. Since mechanical stress is a well‐established inducer of bone growth, volume increases caused by the rapid accumulation of corrosion products and the resulting force development could be a key mechanism and provide an explanation for the observed stimulatory effects of magnesium‐based implants in hard tissue. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 697–709, 2017.